2022
DOI: 10.1021/acs.energyfuels.2c03240
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Field Modeling of Pore-Scale Oil Replacement by Spontaneous Imbibition in Fractured Porous Media

Abstract: Horizontal wells with complicated fracture networks have become a key technical measure to improve the oil recovery of low-permeability and tight reservoirs in China. Spontaneous imbibition is regarded as the major oil recovery mechanism after fracturing. Due to the limitation of the observation scale, the traditional experimental methods cannot accurately describe multiphase fluid flow in the micro-/nanopore space of low-permeability and tight reservoirs, and the pore-scale oil recovery mechanism during spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…According to Schlumberger Business Consulting, the technically recoverable reserves tight oil worldwide are approximately 28–63 billion tons (as shown in Table ). Time magazine believes that the world’s highest tight oil reserves are 42 billion tons . BP pointed out that North America has approximately 10 billion tons of tight oil resources, making it the largest region in the world with tight oil resources .…”
Section: Global Tight Oil Resources and Distributionmentioning
confidence: 99%
“…According to Schlumberger Business Consulting, the technically recoverable reserves tight oil worldwide are approximately 28–63 billion tons (as shown in Table ). Time magazine believes that the world’s highest tight oil reserves are 42 billion tons . BP pointed out that North America has approximately 10 billion tons of tight oil resources, making it the largest region in the world with tight oil resources .…”
Section: Global Tight Oil Resources and Distributionmentioning
confidence: 99%
“…Previous studies [4][5][6] indicated that spontaneous imbibition is one of the primary underlying mechanisms for crude oil extraction in the tight oil reservoir. In recent years, a large number of researchers have adopted the development method of "horizontal well + volume fracturing + shut-in well" to develop tight oil, which involves immediately shutting down the well after volume fracturing and shutting it for a period of time before opening the well for production.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerical simulations of multiphase flow have some limitations. For instance, the modeling process is restricted by severe computational space . It often discretizes complex porous structures into connected pore elements, which are affected by the element’s density and size.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, extensive explorations of the imbibition mechanisms were conducted through numerical simulation, core experiments, and microfluidic models. In numerical simulations, various modeling methods have been employed to investigate the imbibition process, including lattice Boltzmann, , molecular dynamics, pore network model, , phase-field modeling, and so on. The numerical simulation makes a remarkable contribution to providing a more precise depiction of fluid dynamics on the pore scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation